Exact order of relative widths of classes W^r_1 in the space L_1 - Parfinovych, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
As n → ∞ the exact order of relative widths of classes W^r_1 of periodic functions in the space L_1 is found under restrictions on higher derivatives of approximating functions.